Evaluation of the morphologic method for the detection of animal and herbal content in minced meat - Javad Sadeghinezhad; Bahador Hajimohammadi; Farkhondeh Izadi; Fatemeh Yarmahmoudi; Rocco Latorre (Czech Journal of Food Sciences, 2015)
The quantitative and qualitative accuracy of the routine histological method for the determination of unauthorised animal and herbal content in minced meat was to evaluated. Laboratory adulterated minced beef meat; each containing 5, 10, 15 and 20% of soya and chicken gizzard was prepared. Then each sample was divided into three parts and four paraffin embedded blocks were prepared from each part. The sections were stained using haematoxylin and eosin, toluidine blue and Masson's trichrome. The histological examination revealed the soya and gizzard tissues clearly in all the samples. The histometrical analysis showed that there was no significant difference between the estimated percentages of both additive tissues and the real related percentages. Overall, neither was there any significant difference between the data of the three parts of each sample and the real percentages. The findings of the present research suggest the histological technique as an effective method for qualitative and quantitative evaluations of minced meat.